Exploring and Developing Geometric Ideas Related to the Concept of Angle Through a Sequence of Microworlds Using Various Digital Tools: Exploring Geometric Ideas Related to the Concept of Angle (Constructionism Conference Proceedings, 2025)
This short paper describes a learning trajectory or activities sequence that aims for middle and lower secondary school students to explore and develop geometric ideas and understanding related to the concept of angle, as well as problem-solving skills. The sequence uses various and complementary digital tools (Bridge Constructor, GeoGebra and Logo); each had distinct purpose and constituted a different epistemological domain that allowed students to engage in constructions where angles could be conceived in different ways. The aim of the sequence is for students to develop knowledge of the classification of angles, means to measure them and understand their relationships (e.g. between inner and rotational angles) in different contexts.